New Insights into Plant Signaling Mechanisms in Biotic and Abiotic Stress - Hamdy Kashtoh; Muhammad Fazle Rabbee; Kwang-Hyun Baek (Plants, 2025)
Plants are constantly challenged by their environments, including both biotic and abiotic stress factors [...]